Respuesta :

First. Let's work with PEMDAS


P means we start with Parentheses

So distribute -3 making your equation
16-3x-18=-2x+17


Since we have like terms, we will combine them making it
-3x-2=-2x+17

Next. Let's move the -2x over to the other side, by adding

x-2=17

Then add two to both sides to get your answer.

x=19
16-3(x+6)=-2x+17

First, expand the brackets:
16-3x+18=-2x+17

Combine like terms:
34-3x=-2x+17

Add 3x to each side:
34=x+17

-34 from each side:
0=x-17

Add 17 to each side:
17=x
x=17

Hope this helps :)